A Case of Elsberg Syndrome in the Setting of Asymptomatic SARS-CoV-2 Infection. Issue 4 (June 2021) - Abrams, Rory M. C.; Desland, Fiona; Lehrer, Helaina; Yeung, Anne; Tse, Winona; Young, James J.; Mendu, Damodara R.; Vickrey, Barbara G.; Shin, Susan C.
Abstract : Abstract: Elsberg syndrome is a rare cause of lumbosacral radiculitis with concomitant thoracic and lumbosacral myelitis that can be seen after an acute or reactivated viral infection. After the initial coronavirus surge in New York City, a 68-year-old man developed progressive lower extremity weakness and a defined sensory level at the lower abdomen. He had highly elevated SARS-CoV-2 IgG antibodies despite an absence of preceding COVID-19 symptoms. Serial electrodiagnostic testing revealed absent lower extremity late responses, with otherwise normal distal sensorimotor conductions. Electromyography revealed active neurogenic changes and reduced motor unit recruitment in the L3–L4 myotomes. Treatment with methylprednisolone and intravenous immunoglobulin was followed by minimal clinical improvement but re-emergence of the lower extremity late responses on electrodiagnostic testing. We report here, to the best of our knowledge, the first case of suspected COVID-19–associated Elsberg syndrome, which expands the spectrum of neuromuscular manifestations associated with SARS-CoV-2 infection and sheds light on ways to approach diagnostic and treatment options for these patients.